Pravo na socìaln’nyj zahist vìd bezrobìttâ : mìžnarodnyj ta nacìonal’nij dosvìd progološennâ - Pilipenko, Pilip; Ranevič, Orest (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In the article, theoretical and practical questions about the proclamation of the right to social protection from unemployment, both at the international and national levels, are investigated. The authors show that in 1934 the world community has already formed a concept of a universal model of social welfare of persons in the situation of unemployment, and has also determined the forms of this system, the basis and conditions for the assignment of social payments to unemployed in social insurance systems. As it is demonstrated, all this servedas further guidance at the national level of different states for the introduction of systems of social insurance in the case of unemployment.At the same time, Ukraine had to honour its intergovernmental commitments in the sphere of social protection of a person from unemployment, so while adopting in 1996 the fundamental law of the state, the right of man to social protection from unemployment was consolidated in article 46 of the Constitution of Ukraine. This right is based on international standards, which define the policy of states in the sphere of social protection of citizens in the case of unemployment.Besides, it is established that the constitutional consolidation of the right to social protection from unemployment comprises the basis of legal regulation in the system of law, which is designed to enforce the legal possibility of a person to social protection from unemployment.According to the fundamental law, the right of citizens to social protection includes the right to security in cases of complete, partial or temporary disability, loss of breadwinner, unemployment circumstances beyond their control, as well as old age and in other cases provided by law. Th us, the Constitution of Ukraine, which has the highest legal force throughout the territory of the Ukrainian state, establishes the right to social protection from unemployment as a constitutional right.As it is revealed, the emergence and establishment of the right to social protection from unemployment is caused by the recognition of states of their social function and it is aimed at overcoming the negative eff ects of social risk of unemployment. Further development and transformation of this right takes place within the limits of national legal systems, which, accordingly, occurs in the legislation of Ukraine. Constitutional proclamation and legislative regulation of the right to social protection of citizens from unemployment, give grounds to assert the existence of an eff ective legal tool, which is designed to ensure its proper realization.Also, the right to social protection from unemployment is considered as the entitlement of a person to receive material support and social services in the event of such social risk as unemployment, as guaranteed by the Constitution and laws of Ukraine, in accordance with its powers.
Keywords: social insurance; social services; material security; employment; employment guarantees